Technological Development in the Algerian University Libraries - Bernaoui, Radia (Qualitative and Quantitative Methods in Libraries, 2019)
Bridging the digital divide is an essential element in the aims of the Algerian University. Equitable access to the scientific heritage of the scientific community is away to ensure the advancement of knowledge and the development of the country. Libraries have become an essential showcase for disseminating knowledge and research results. Academic digital libraries are a part of library services using new technologies to provide access to digital collections and to answer to the needs of the information society. So, we are interested in the technological development of the university libraries of the higher national schools in Algeria.